Evaluating The Impact Of 5Cs Model Factors And Marketing Mix Analysis: A Case Study - Marko SUBOTIĆ; Marko VULIĆ; Bojan S. RISTIĆ; Nevenka POPOVIĆ – ŠEVIĆ; Aleksandar ŠEVIĆ; Milena ILIĆ P. (Communications of International Proceedings, 2021)
Tourism belongs to the branch of the economy (tertiary sector), which includes work with people (service processes), and brings numerous benefits to the population, economy, and society, participates in a significant share in the gross domestic product and increases employment. If we analyse the history of tourism, the current situation and anticipate future trends based on what we have learned, it can be said with certainty that tourism will always be a significant factor in the development of society and national and regional economies. Tourism will continue to perform its functions, and people around the world will achieve a constantly larger amount of tourist travel, visits to tourist destinations, and the number of overnight stays, which is an important indicator of tourist traffic. People from all over the world will embark on tourist trips to get to know different localities and cultures for the sake of sports, health, vacation, adventure, gourmet events, sustainability, and the like. In the future, due to the Covid-19 pandemic, a greater focus of tourists on the natural and cultural beauties of national countries can be expected. From the point of view of the majority of citizens, travel for vacation is an expression that is used in most cases when one wants to express the need to change the surroundings, which is further converted to an individual or collective stay outside the place of residence for more than two days according to the tourist definition. There are several reasons for tourists to travel, from the desire to escape from everyday life and everything that is associated with a normal lifestyle to experiencing something completely new and unique. Therefore, it is not surprising that countries that are recognised worldwide as tourism leaders are investing additional funds in developing their tourist offers and capacities to enrich the already versatile offer even more. It is the same with the efforts of countries that are not tourism leaders but have the aspiration to enrich their tourist offers. The paper deals with the analysis of the selected marketing strategy and marketing mix of the tourist destination Country Club Zdravkovac, its observation, and recording.
Keywords: Brand Recognition; Marketing Strategy; Marketing Mix; Situation Analysis.